2019
DOI: 10.29333/ejeph/5975
|View full text |Cite
|
Sign up to set email alerts
|

HIV Prevalence and Related Risk Behaviors among Men Who Have Sex with Men in Kinshasa, the Democratic Republic of the Congo

Abstract: The purpose of this study was to determine the prevalence of HIV and syphilis and examine the HIV-related behaviors among men who have sex with other men (MSM) in Kinshasa, Congo. A modified snowball sampling was used to recruit the participants. The results showed that among the 401 men studied, 23.7% and 11.2% were infected with HIV and syphilis, respectively. HIV risk behaviors were rampant in this population. In the last 6 months preceding the survey, 83.3% of MSM reported receptive anal sex (RAS) with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
1
0
1
Order By: Relevance
“…The sexual risk behaviors of MSM OFW include being diagnosed with sexually transmitted diseases; do sexual acts with partners whom they guess are HIV negative; engage in specific sexual behaviors such as oral and anal sex; use condoms for anal sex; prefer relationships with bisexual, homosexual and heterosexual gender orientations; have multiple number of partners in the past five years; engage in commercial sex; and some MSM use sex toys during sexual relations. A study (Inungu et al, 2019) confirmed in a cohort that HIV risk behaviors were common. 83.3 percent of MSM reported receptive anal sex (RAS) in the six months before the study, with an average of seven sexual partners.…”
Section: Discussionmentioning
confidence: 88%
“…The sexual risk behaviors of MSM OFW include being diagnosed with sexually transmitted diseases; do sexual acts with partners whom they guess are HIV negative; engage in specific sexual behaviors such as oral and anal sex; use condoms for anal sex; prefer relationships with bisexual, homosexual and heterosexual gender orientations; have multiple number of partners in the past five years; engage in commercial sex; and some MSM use sex toys during sexual relations. A study (Inungu et al, 2019) confirmed in a cohort that HIV risk behaviors were common. 83.3 percent of MSM reported receptive anal sex (RAS) in the six months before the study, with an average of seven sexual partners.…”
Section: Discussionmentioning
confidence: 88%
“…Es necesario tomar en cuenta que, de acuerdo a las características de los participantes, a pesar de que uno de los criterios de selección fue que no consumieran drogas, quienes tienen ITS, en su mayoría, manifestaron que consumen ocasionalmente alcohol. El uso indebido del alcohol aumenta el riesgo de las conductas sexuales de riesgo y de VIH (Delgado et al, 2017;Dir et al, 2018;García et al, 2017;Kitwein & Looby, 2018;Walsh et al, 2017); por tanto, el control para el consumo de alcohol evita el contagio venéreo estrechamente vinculado a su ingesta (Inungu et al, 2020;Díaz, 2012;Fernández, 2014). Aun cuando los participantes de la investigación refirieron un consumo esporádico de alcohol, es pertinente sugerir que futuros estudios en HSH con un consumo habitual de alcohol o drogas, deben incluir abordajes multidisciplinarios, que aborden otros objetivos, tomando en cuenta las intervenciones existentes sobre consumo de sustancias psicoactivas para HSH (Charlebois et al, 2017;Mausbach et al, 2007).…”
Section: Discussionunclassified